2011
DOI: 10.1371/journal.pone.0019015
|View full text |Cite
|
Sign up to set email alerts
|

Two Theileria parva CD8 T Cell Antigen Genes Are More Variable in Buffalo than Cattle Parasites, but Differ in Pattern of Sequence Diversity

Abstract: Background Theileria parva causes an acute fatal disease in cattle, but infections are asymptomatic in the African buffalo (Syncerus caffer). Cattle can be immunized against the parasite by infection and treatment, but immunity is partially strain specific. Available data indicate that CD8+ T lymphocyte responses mediate protection and, recently, several parasite antigens recognised by CD8+ T cells have been identified. This study set out to determine the nature and extent of polymorphism in two of these antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
179
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 64 publications
(208 citation statements)
references
References 43 publications
27
179
2
Order By: Relevance
“…This is consistent with Tp1 and Tp2 sequencing data from laboratory-maintained parasite isolates, which have shown that sequences remain identical following tick passage of the parasites (R. Pelle, unpublished observations). Recent analyses of Tp2 nucleotide sequences have revealed evidence of positive selection at the codon level over the length of the gene, but the failure to detect obvious enrichment for positively selected residues within six defined epitopes compared with the remainder of the sequence suggested that the changes may not be due to immune selection (34). However, immune selection may not be detectable by this approach if the Tp2 protein contains a large number of additional undefined CD8 + T cell epitopes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with Tp1 and Tp2 sequencing data from laboratory-maintained parasite isolates, which have shown that sequences remain identical following tick passage of the parasites (R. Pelle, unpublished observations). Recent analyses of Tp2 nucleotide sequences have revealed evidence of positive selection at the codon level over the length of the gene, but the failure to detect obvious enrichment for positively selected residues within six defined epitopes compared with the remainder of the sequence suggested that the changes may not be due to immune selection (34). However, immune selection may not be detectable by this approach if the Tp2 protein contains a large number of additional undefined CD8 + T cell epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent analyses of field isolates of T. parva confirmed that both of these epitopes are polymorphic. The Tp2 Ag was found to be particularly variable, exhibiting substitutions in .70% of the amino acid residues, resulting in 23 allelic variants of the dominant A10-restricted epitope (Tp2 [49][50][51][52][53][54][55][56][57][58][59] ) among the 80 sequences examined (34). This unique set of naturally occurring parasite epitope variants provides a useful resource both to dissect the basis of strain specificity of the CD8 + T cell response and to investigate potential selective forces in generating polymorphism.…”
Section: D8mentioning
confidence: 99%
See 1 more Smart Citation
“…The Naegleria DNA still practices such transformations of its host (617,618). Later, in the unicellular parasite Theileria under immunological attack in an invaded bovine host, the most versatile theileria DNA encodes an elaborate physiology for the parasite to evade that immunological attack from its host (619). In the theileriainduced fatal lymphoproliferative disease, the East Coast fever, the parasite induces NFκB to secure apoptosisfree state of the schizontinfected lymphocytes.…”
Section: Mechanisms Of Inflammatory Carcinogenesismentioning
confidence: 99%
“…In-depth studies for T. parva are at an early stage due to lack of informative high-resolution markers. The approaches previously used to dissect T. parva parasite polymorphism and recombination events include monoclonal antibodies [9], gene probes binding to multi-copy loci [5], panels of micro- and mini-satellite markers [10,11] and most recently the sequence polymorphism in antigens that are targets of CD8+ T cell responses [12]. While useful to generate preliminary information, these techniques were unable to provide high resolution dissection of recombination events at the whole genome level.…”
Section: Introductionmentioning
confidence: 99%